Henry : a Polish swimmer's true story of friendship from Auschwitz to America - Shawver, Katrina (2017)
"When Katrina Shawver met the eighty-five year old Henry Zguda, he possessed an exceptional memory, a surprising cache of original documents and photos, and a knack for meeting the right people at the right time. Couched in the interview style of Tuesdays with Morrie, Henry relates in his own voice a life as a champion swimmer and swimming coach, interrupted by three years imprisoned in Auschwitz and Buchenwald as a Polish political prisoner. Told with a pragmatic gallows humor, and sense of hope, this bridge to history is supported by extensive research, original documents, and rare photos. Ultimately, Henry is the story a resilient young man who survives by his wits, humor, friends, and a healthy dose of luck"--Page [4] of cover.